Influenza A–induced rhabdomyolysis with acute renal failure following a deep tissue massage. Issue 5 (3rd September 2021) - Dickey, Brandon; Swanson, Eric M.; Brigmon, Matthew; Siller, Alfredo
Abstract: We describe a unique case of severe influenza A–induced rhabdomyolysis in a previously healthy 39-year-old man, who developed symptoms immediately following a 2-hour deep-tissue massage and improved with oseltamivir and intravenous fluids. This case describes a possible temporal association between tissue damage secondary to deep tissue massage and the subsequent exacerbation of rhabdomyolysis in the setting of an influenza A infection. Biological evidence of muscle cell viral invasion with massage supports the possibility of elevated influenza A pathogenicity.